(untitled) (Journal of Technology and Operations Management, 2018)
Job turnover is traditionally faced by organisations in many industries. Implications such as resources wastage and low productivity can be derived from the turnover issue. The turnover intention was found to be a reliable predictor for actual turnover in previous studies. Consequently, this demands some insights on turnover intention issue, especially within the Malaysian context. This paper will focus on determining the relationship of transactional leadership styles on turnover intention among manufacturing operators, particularly in Electrical and Electronics sub-sector. The study was conducted amongst the operators of manufacturing industry in Peninsular Malaysia (N=800). Considering that Malaysia manufacturing industry has shown a strong economic growth through substantial investment in economic activities, it is essential for all manufacturing companies to retain talented employees and reduce the turnover problem in order to be more productive and competitive. The findings had accepted the research hypothesis. Dimensions of transactional leadership styles (i.e. contingent rewards, management-by-exception passive) significantly correlated and contributed to the turnover intention. The findings had contributed to the theoretical significance through the examination of direct relationships between transactional leadership styles on turnover intention among local operators in the manufacturing sector in Malaysia.